2021
DOI: 10.1159/000520297
|View full text |Cite
|
Sign up to set email alerts
|

Trichoscopic Signs in Dermatomyositis, Systemic Lupus Erythematosus, and Systemic Sclerosis: A Comparative Study of 150 Patients

Abstract: <b><i>Background:</i></b> Hair and scalp involvement is prevalent in connective tissue diseases (CTDs). Trichoscopic features may provide a diagnostic implementation and enable differentiation among CTDs; however, a direct comparison of these signs among CTD patients is lacking. <b><i>Objectives:</i></b> To compare trichoscopic findings in dermatomyositis (DM), systemic lupus erythematosus (SLE), and systemic sclerosis (SSc) as well as determine their distinctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It is worth noting that DM shows some dermoscopic similarities with lupus erythematosus (LE). In a recent study by Chanprapaph et al [17] on trichoscopic findings in CTDs, a decrease in the hair shaft number, presence of white dots, brown honeycomb pattern, white patches, interfollicular scales, dotted vessels, and thin or thick arborizing vessels was observed with comparable frequency in DM and systemic lupus erythematosus (SLE). On the other hand, perifollicular red-brown pigmentation, perifollicular scaling, and tortuous dilated capillaries, referred to by the authors as "microaneurysmal blood vessels", were found to be specific for DM, while hair shaft hypopigmentation was significantly more common in SLE.…”
Section: Discussionmentioning
confidence: 97%
“…It is worth noting that DM shows some dermoscopic similarities with lupus erythematosus (LE). In a recent study by Chanprapaph et al [17] on trichoscopic findings in CTDs, a decrease in the hair shaft number, presence of white dots, brown honeycomb pattern, white patches, interfollicular scales, dotted vessels, and thin or thick arborizing vessels was observed with comparable frequency in DM and systemic lupus erythematosus (SLE). On the other hand, perifollicular red-brown pigmentation, perifollicular scaling, and tortuous dilated capillaries, referred to by the authors as "microaneurysmal blood vessels", were found to be specific for DM, while hair shaft hypopigmentation was significantly more common in SLE.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, this is the one with the highest number of cases. Chanprapaph et al [ 26 ] recently compared trichoscopic findings in DM, systemic lupus, and systemic sclerosis patients. They found that perifollicular reddish-brown pigmentation and the presence of blood vessels with microaneurysms were present exclusively in DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Another mechanism is that SCLE may be stimulated by ultraviolet (UV)-B radiation resulting in translocation of Ro (SSA) antigen and increase of cell membrane antigen expression via epitope spreading. [13][14][15] Our patient frequently engaged in outdoor activities with inadequate photoprotection which may have aggravated the symptoms. 16 Lastly, focusing on mechanism of action, anti-PD-1 or PD-L1 may modulate humoral immunity which enhances pre-existing autoantibodies and unmask latent auto-immunity.…”
Section: Dovepressmentioning
confidence: 94%